On the measurement of competency - Shavelson, Richard J. [Verfasser] (My University, 2010)
"Across multiple societal sectors, demand is growing to measure individual and group competencies. This paper unpacks Hartig et al.'s (2008) competency definition as a complex ability construct closely related to real-life-situation performance to make it amenable to measurement. Unpacked following the assessment triangle (construct, observation, inference), competency measurement is exemplified by research from business, military and education sectors. Generalizability theory, a statistical theory for modeling and evaluating the dependability of competency scores, is applied to several of these examples. The paper then pulls together the threads into a general competency measurement model." (Autorenreferat, BIBB-Doku)
Keywords: L 6.3.1 Diagnose- & Messinstrumente; Kompetenz; Kompetenzbegriff; Kompetenzfeststellung; Kompetenzbewertung